FACTORS AFFECTING CONSUMER AWARENESS TOWARDS CAMEL MILK USING BINARY LOGISTIC REGRESSION - NITISH KUMAR SINGH*, HARISHCHANDRA SINGH RATHOD; M. V. ALAGAWADI (The Journal of Research ANGRAU, 2021)
Camel milk is rich in nutrition, vitamins and is widely accepted for treating diseases. The study aimed to measure the awareness level among the consumers towards Camel milk. The study used an exploratory research approach and judgmental sampling technique for data collection in Gandhinagar, Gujarat. Binary logistic regression was performed to determine the socio-demographic factors that affect consumer awareness towards Camel milk.The study reported that awareness of Camel milk among the respondents was around seventy percent from the sampled responses. The study was performed during the period December 2020 and includes 388 respondents (Mean=30 and SD= 1.85). The findings recorded that only education is essential in raising consumer awareness of camel milk. The marketer should focus on creating awareness about the benefits of using camel milk and its palatability.